Purchase Intention Of Glowsophy Moisturizer on Tiktok: Influencer Reputation As Moderator And Kols Customer Perception - Esa Agata; Wenny Pebrianti; Bintoro Bagus Purmono; Heriyadi Heriyadi; Harry Setiawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
TikTok is a rapidly growing social media platform in Indonesia and plays a crucial role in digital marketing, particularly in the skincare industry. Intense competition and negative issues such as black campaigns require companies to adopt effective and credible marketing communication strategies. This study aims to empirically examine the effects of social media marketing activities, perceived quality of information, and KOLs customer perception on purchase intention, as well as the moderating role of influencer reputation for Glowsophy Moisturizer on TikTok. This study employs a quantitative approach using a survey of 200 TikTok users in Indonesia. Data were collected through online questionnaires and analyzed using PLS-SEM with SmartPLS 4.0. The findings indicate that all independent variables have positive and significant effects on purchase intention. Furthermore, influencer reputation significantly strengthens the relationships between the independent variables and purchase intention. The study highlights the importance of social media marketing activities, information quality, and influencer reputation in enhancing consumers’ purchase intention, particularly when brands encounter negative issues.